An introduction to the sociology of health and illness - White, Kevin, 1955-; Sage eBooks (London : SAGE, 2002)
Kevin White argues that a range of sociological causes are behind much illness. The author's study shows how the dynamics of class, gender and ethnicity are inextricably linked to health and illness in modern societies.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social medicine; Electronic books